Toward Robust Segmented Nanowires: Understanding the Impact of Crystallographic Texture on the Quality of Segment Interfaces in Magnetic Metallic Nanowires. Issue 18 (8th August 2016) - Zhang, Jin; Pané, Salvador; Sort, Jordi; Pellicer, Eva
Abstract : Segmented nanowires (NWs) have found a wealth of applications due to their multifunctionality, arising from complementarities and synergies among segments of different materials. However, to ensure a practical use of segmented NWs, high quality interfaces between segments must be ensured. Herein, trisegmented CoPt/Cu/Ni NWs and bisegmented CoPt/Ni magnetic NWs are fabricated by means of template‐assisted electrodeposition and the characteristics of their interfaces are investigated in detail. The presence of a Cu segment sandwiched between the CoPt and the Ni segments severely affects the integrity of the whole NW. Namely, Cu deposits in a (200) textured face‐centered cubic (fcc) structure, which cannot accommodate well on the c ‐axis oriented hexagonal close‐packed CoPt. Instead, when the Cu segment is absent, well‐connected CoPt/Ni NWs with smooth interface are obtained. Unlike the Cu segment, Ni shows the (111) textured fcc structure, which holds good crystallographic matching with the underlying CoPt segment. Magnetic measurements reveal that CoPt/Ni NWs exhibit staircase‐like hysteresis loops similar to the trisegmented CoPt/Cu/Ni NWs. Such loop shape stems from the dissimilar coercivity between the hard (CoPt) and soft (Ni) segments. The bisegmented NWs (with robust interfaces) are appealing for multibit recording media, magnetic nanoelectromechanical systems, and magnetically driven drug delivery nanoplatforms. Abstract : High quality interfaces in segmented nanowires are crucial for reliable practical applications. The CoPt/Ni and CoPt/Cu interfaces in electrodeposited CoPt/Ni and CoPt/Cu/Ni magnetic nanowires grown by template‐assisted electrodeposition are studied in detail. While robust and smooth interfaces develop for CoPt/Ni, porous and cracked junctions are observed for CoPt/Cu due to severe lattice mismatch.